Topical antifungals: A review and their role in current management of dermatophytoses - Shital Amin Poojary (Wolters Kluwer Medknow Publications, 2017)
Topical antifungals are an important adjuvant in treatment of dermatophytosis. Also specific situations such as dermatophytoses in pregnancy and infants often warrant topical therapy. Several new topical antifungals and newer formulations hold out the promise of enhanced effectiveness of topical therapy in dermatophytosis. This article reviews the entire spectrum of topical antifungals and formulations and their role in management of dermatophytosis.